Do inclusive education policies improve employment opportunities?: evidence from a field experiment - Monge Agüero, Jorge; Galarza, Francisco; Yamada Fukusaki, Gustavo (Universidad del Pacífico. Centro de Investigación, 2020)
In labor markets where disadvantaged students are discriminated against, merit-based college scholarships targeting these students could convey two opposing signals to employers. There is a positive signal reflecting the candidate’s cognitive ability (talented in high-school and able to maintain a high GPA in college) as well as her soft skills (overcoming poverty). There is also a possible negative signal as the targeting of the scholarship indicates that the beneficiary comes from a disadvantaged household. We conduct a correspondence study to analyze the labor market impact of an inclusive education program. Beca 18 provides merit-based scholarships to talented poor students admitted to 3-year and 5-year colleges in Peru. We find that the positive signal dominates. Including information of being a scholarship recipient increases the likelihood of getting a callback for a job interview by 20%. However, the effect is much smaller in jobs and careers where the poor are under-represented, suggesting that the negative signal of the scholarship is not zero.